Rancang Bangun Sistem Kontrol Elektro Pneumatik Pada Alat Bantu Pemotong Green stick tube - Syifa Amalia Azzahra Putri Wardoyo; Henry Prasetyo; Arif Cahyono, M. Ridwan; Susilawati, Dera (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
The current process for cutting green stick tubes at the company is still done manually by operators using scissors because the extruder machine cannot cut sizes below 1,000 mm. As a result, sizes 6.00-9 and 6.50-10 must be cut manually before the splicing process. The green stick tubes coming out of the extruder often exceed the splicing machine’s cutting tolerance of 20 mm. According to the data, sizes 6.00-9 and 6.50-10 with a length of 1010 mm need to be cut to 840 mm and 910 mm, respectively. The average cutting time per shift is 164.6 seconds, influenced by the time operators take to find scissors and the lack of efficient cutting tools. The main issues in this cutting process are caused by three factors: Machine, Material, and Man. The extruder machine cannot cut green stick tubes smaller than 1,000 mm. The green stick tube material of sizes 6.00-9 and 6.50-10 needs to be cut because their length exceeds the requirement. Additionally, inconsistencies among operators when cutting occur due to the lack of proper tools or guides. To address these issues, a cutting aid tool using a heater and pneumatic system is designed. This tool is expected to facilitate the cutting process of green stick tubes. The design of this tool aims to overcome the extruder machine’s inability to cut smaller sizes, reduce unnecessary additional time, ease the cutting process for operators, decrease the variation in cutting time, and improve the workflow in the splicing section, so the green stick tubes can be processed directly without additional hindrances.